PARTISIPASI MASYARAKAT DALAM UPAYA PEMANFAATAN LIMBAH TAHU DI KECAMATAN BANDUNGAN, KABUPATEN SEMARANG - Arif Sofianto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2017)
Bandungan subdistrict, Semarang regency is one of the main industrial centers of tofu industry. Liquid waste out of tofu industry potentially to be processed into biogas, on the other hand if it is not managed will be the environmental contamination. Government of Semarang District has been providing assistance 2 units of biogas processing equipment to